Cattaneo–Christov heat flux theory toward the magnetohydrodynamic micropolar hybrid nanofluid flow past a stretching/shrinking sheet with non‐uniform heat source/sink and thermal radiation. Issue 10 (13th July 2022) - Algehyne, Ebrahem A.; Alrihieli, Haifaa F.; Saeed, Anwar; Dawar, Abdullah; Kumam, Poom
Abstract: In this investigation, a 2D flow of micropolar hybrid nanofluid (HNF) is considered over stretching/shrinking sheet. The magnetic effect is employed in a perpendicular direction to the surface of sheet. To improve the thermal conductivity of the fluid flow, the nanoparticles (NPs) of iron oxide and graphene oxide are mixed with water to obtain the HNF and water is used as a base fluid ( F e 3 O 4 + GO / H 2 O ) $\;( {{\rm{F}}{{\rm{e}}_3}{{\rm{O}}_4} + {\rm{GO}}/{{\rm{H}}_2}{\rm{O}}} )$ . The proposed equations of the modeled problem are converted to dimensionless form by implementing the similar variables. The analytical solution of the modeled equations is evaluated by mean of homotopy analysis method. The impacts of the embedded constraints on the HNF flow profiles are discoursed theoretically by incorporating a graphical view. Special cases (stretching, shrinking) are considered for the HNF in order to examine the impacts of the embedded parameters on the HNF flow profiles. The results showed that the expanding values of the stretching parameter, the HNF flow particles are pushed in a forward direction due to which fluid moves swiftly for both shrinking/stretching cases. The velocity profiles are increased with the increasing material parameter for the stretching case, while a reducing impact is found for the shrinking case. Also, the increasing material parameter enhances the microrotation profiles the HNF flow. Furthermore, the material parameter shows the same behavior for both stretching and shrinking cases. The increasing volume fraction of the solid NPs reduces the velocity profiles for stretching case, while augments for shrinking case. On the other hand, it is observed that the increasing volume fractions of the NPs increase the microrotation and temperature profiles for both stretching and shrinking cases. Abstract : In this investigation, a 2D flow of micropolar hybrid nanofluid (HNF) is considered over stretching/shrinking sheet. The magnetic effect is employed in a perpendicular direction to the surface of sheet. To improve the thermal conductivity of the fluid flow, the nanoparticles (NPs) of iron oxide and graphene oxide are mixed with water to obtain the HNF and water is used as a base fluid ( F e 3 O 4 + GO / H 2 O ) $\;( {{\rm{F}}{{\rm{e}}_3}{{\rm{O}}_4} + {\rm{GO}}/{{\rm{H}}_2}{\rm{O}}} )$ . The proposed equations of the modeled problem are converted to dimensionless form by implementing the similar variables.…